Translation Techniques of Assertive Speech Act in Frozen II Movies Subtitle - Agista, Rifa; Oktoviandry, Rifki (English Language and Literature, 2024)
This research entitles “Translation Techniques of assertive speech acts in Frozen II movies subtitles”. This research aims to determine the types of assertive speech acts and the types of translation techniques for this film. Researcher used Yule theory (1996) in analyzing speech and the theory of translation techniques by Molina and Albir (2002). This research uses qualitative methods in analyzing data. Researcher found 34 data regarding assertive speech acts. The results of this research are 6 types of directive speech acts found in the speech of this film. This research also found nine types of translation techniques used by translator to translate utterance that contains assertive speech acts. The results of data analysis show that the dominant type of translation technique used by translators in translating assertive speech acts is the establish equivalent with 9 data (26%).